Governing the Voice: A Critical History of Speech-Language Pathology - Joshua St. Pierre; Charis St. Pierre (Foucault Studies, 2018)
This essay argues that Speech-Language Pathology (SLP) emerged as a response to the early twentieth-century demand for docile, efficient, and thus productive speech. As the capacity of speech became more central to the industrial and democratic operations of modern society, an apparatus was needed to bring speech under the fold of biopower. Beyond simple economic productivity, the importance of SLP lies in opening the speaking subject up to management and normalization—creating, in short, biopolitical subjects of communication. We argue that SLP accordingly emerged not as a discreet institution, but as a set of practices which can be clustered under three headings: calculating deviance, disciplining the tongue, and speaking the truth of pathologized subjects.